2015
DOI: 10.1007/s00234-015-1634-1
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured basilar artery perforator aneurysms—treatment regimen and long-term follow-up in eight cases

Abstract: Conservative management of ruptured BA aneurysms might be a first-line treatment option with common spontaneous aneurysm occlusion, low rate of re-SAH, and promising clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…ORs and 95% CI for each prespecified outcome were calculated accordingly. No particular heterogeneity or publication bias analysis was reported because the maximum number of cases per published series was eight 8. All statistical tests were performed using SPSS (IBM, Armonk, New York, USA).…”
Section: Methodsmentioning
confidence: 99%
“…ORs and 95% CI for each prespecified outcome were calculated accordingly. No particular heterogeneity or publication bias analysis was reported because the maximum number of cases per published series was eight 8. All statistical tests were performed using SPSS (IBM, Armonk, New York, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Although the cases reported so far are all caused by SAH, there are no reports of unruptured cases, so the natural history of BAPA is not clear [26].Because of the small size of the aneurysm,it is di cult to complete superselective artery embolization Because of the small size of the aneurysm, On the other hand,The aneurysm is located at the deep end, which makes it di cult to expose.Ischemic events caused by di culties in perforating perforating branches are all problems to be considered when choosing a treatment plan.However,some cases were found to be self-healing during follow-up, so conservative observation under DSA follow-up was the preferred method in many reports [16].Rehaemorrhage occurred in 6 of the 21 conservative cases reported in the literature (28.57%), of which 2 received microsurgery and 2 received endovascular intervention. (1 cases were treated with coil embolization, and 1 case were implanted with ow diverter).2 cases remained conservative.Of the 4 patients receiving intervention, only 1 recovered well, and the other 3 had neurological dysfunction of varying degrees due to perforator ischemic events.2 patients who received conservative treatment recovered well.This result proves that the effect of active intervention may not be better than conservative observation [5,6,11,20,24].…”
Section: Discussionmentioning
confidence: 65%
“…The di culty of endovascular interventional therapy is that superselective microaneurysms with microcatheters are prone to rupture and bleeding, and the perforating arteries are too small to be effectively protected.Of the 3 cases reported in the literature with coils and 2 cases with Onyx embolization, only one had a good recovery from distal perforator aneurysms of the main basilar artery and the rest had hemiplegia of varying degrees caused by perforator ischemic events [9,13,20].Therefore, although it has been reported that the perforator artery as the parent artery can be compensated [29], whether it can be safely occluded remains to be discussed.Another option to consider is stent placement in the basilar artery.The hemodynamic study of aneurysm model showed that the blood ow velocity, eddy current and wall shear stress in the aneurysm cavity were signi cantly changed after the stent was implanted into the aneurysm neck.And the denser the mesh, the greater the impact [30].accordingly,FD seems to be an ideal choice, but this is not the case.The incidence of perforating infarction after posterior circulation aneurysms treated with FD was 14% [31].Only one of the ve FD BAPAs (4 with Pipeline and 1 with SILK) in the literature had no ischemic events.It is suggested that excessive hemodynamic changes may be a risk factor for perforator occlusion [15,19,24].To this end, more patients try to choose the conventional stent-in-stent technique (Enterprise, Neuroform, Leo) for treatment.Half of the 10 reported patients had no de nite ischemic events (the other 5 had no de nite prognosis), suggesting that this technique may be a better choice for BAPA intervention [12,21,26] .However, whether antiplatelet therapy will increase acute hemorrhagic complications remains to be seen in larger cases and longer-term followup.…”
Section: Discussionmentioning
confidence: 99%
“…rPCPAs are extremely rare vascular malformations with very small dimensions, low blood flow,7 and frequent delayed filling at conventional DSA. These features indicate a high risk of rPCPA under diagnosis, which is confirmed by a first negative DSA observed in 71% of cases in our series.…”
Section: Discussionmentioning
confidence: 99%
“…This result is interesting, especially with a 14% risk of infarction of the perforator artery with FDs10 compared with the risk of permanent ischemic complications associated with the surgical approach of up to 75%11 or other endovascular options including coils and embolic agents 12. In the case of coiling, the microcatheter rarely fits the rPCPA dimensions, while with liquid agent embolization (ie, Onyx) there is a risk of non-target vessel occlusion as well as perforator occlusion with pontine stroke and potential SAH bleeding,7 13 making these treatment options probably more hazardous than FDs.…”
Section: Discussionmentioning
confidence: 99%